Combustion synthesis of Co-Cu-Mn oxides deploying different fuels - Gardey Merino, María Celeste (2015)
Ternary spinel-like oxides such as CuFeMnO4, CoCuMnOxand CuCr2O4are attractive materials due to their absorbent properties when used as pigments for selective surfaces thus improving solar heaters efficiency. These materials are obtained through sol-gel and sol-gel-combustion methods. This work proposes the synthesis of mixed oxides of Co, Cu and Mn by means of original one-step stoichiometric combustion methods starting from Mn(NO3)2,Co(NO3)26H2O, Cu(NO3)23H2O and Aspartic acid (Asp) or Lysine(Lys) as fuels. The resulting ashes after the combustion were calcined at 500 °C. The obtained ashes and the calcined powders were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and by Brunauer–Emmett– Teller method (BET), and TG-DTA analysis. In calcined powders obtained with Lys (CoCuMnOx-Lys), the phase corresponding to CoCuMnOxand others segregated phases were identified. However, in calcined powders obtained with Asp (CoCuMnOx-Asp) only the phase corresponding to CoCuMnOxwas identified. The sample CoCuMnOx-Lys presented an average crystallite size of 44 nm and a specific surface area of 23 m2/g while in CoCuMnOx-Asp, 54 nm and 13 m2/g values were obtained throughout FT-IR vibrational modes associated with spinel metallic oxides for both calcined powders (Asp and Lys) were observed. Additionally, by means of TEM, polyhedral particles with an average size of 20 to 100 nm were observed. In particular, it was determined in CoCuMnOx-Lys an average size of 44nm. According to the different fuels used (Asp and Lys), an evident variation in the obtained phases was observed. However, it was not obtained any difference in crystallite size and specific area surface values. It is of considerable importance the study of further syntheses processes to verify this trend.